2009
DOI: 10.1080/13816810802454081
|View full text |Cite
|
Sign up to set email alerts
|

Macular Dysfunction and Morphology in Spinocerebellar Ataxia Type 7 (SCA 7)

Abstract: The patients with genetically confirmed SCA 7 presented an early macular dysfunction, preceding any signs of abnormalities in fundus appearance. According to the electrophysiological findings the primary dysfunction involves the cone photoreceptors in the foveal region, however in an older patient involvement of cone photoreceptors throughout the retina was verified. This is in accordance with the theory that ataxin-7 interacts with CRX transcription, since it is known that mutations in the CRX gene cause cone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…In our first patient, who had more severe visual loss, there was very subtle pigmentary mottling in the macular regions and possibly mild temporal optic disc pallor. Review of fundus photographs from previously reported SCA-7 patients, in which the ocular fundi were considered normal, suggests that subtle abnormalities, such as retinal arterial attenuation, may have been present but overlooked 12. A prospective study of individuals with the SCA-7 mutation is required to further delineate the sequence of ocular fundus changes in relation to symptom onset and visual function parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In our first patient, who had more severe visual loss, there was very subtle pigmentary mottling in the macular regions and possibly mild temporal optic disc pallor. Review of fundus photographs from previously reported SCA-7 patients, in which the ocular fundi were considered normal, suggests that subtle abnormalities, such as retinal arterial attenuation, may have been present but overlooked 12. A prospective study of individuals with the SCA-7 mutation is required to further delineate the sequence of ocular fundus changes in relation to symptom onset and visual function parameters.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Furthermore, patients may eventually develop other neurologic deficits, including loss of manual dexterity, speech dysarthria, dysphagia, and eye movement abnormalities. 2 A number of neuropathologic studies have documented the anatomic consequences of the neurodegenerative process. These include severe degeneration of the cerebellar cortex and other cortical regions.…”
mentioning
confidence: 99%
“…1 SCA7 is considered one of the rarest forms of genetic autosomal dominant cerebellar ataxia. 2 Clinically, SCA7 is characterized by a combination of cerebellar ataxia and macular degeneration and is the only spinocerebellar ataxia that manifests in permanent blindness. 3,4 Furthermore, patients may eventually develop other neurologic deficits, including loss of manual dexterity, speech dysarthria, dysphagia, and eye movement abnormalities.…”
mentioning
confidence: 99%
“…In this instance, OCT imaging was essential to diagnosis. Earlier papers have reported retinal thinning on OCT in patients with SCA7 5,6 . The OCT for Patient 3 demonstrates outer retinal atrophy with loss of the outer nuclear layer and ellipsoid zone in the central macula.…”
Section: Discussionmentioning
confidence: 93%